Cover page and Editorial - Syed Alunad, Sharifah Suhanah (Journal of Malaysian and Comparative Law, 2019)
Editorial Note We bid farewell to 2019 with this edition which sees two significant notes on Malaysian cases. The first is JRI Resources Sdn Bhd v Kuwait Finance, where the Federal Court delivered a landmark decision on Islamic banking and finance through a majority decision which declared that ss 56 and 57 of the Central Bank of Malaysia Act 2009 was constitutional, and that the Syariah Advisory Council's role was merely to ascertain and determine Islamic law, not to decide the case. The second is Anthony Bourke & Anor v CIMB Bank Bhd, where the Federal Court invalidated an all-encompassing exclusion clause in a loan agreement for being contrary to s 29 of the Contracts Act 1950 and the doctrine of public policy which underpins s 29. Last but not least is Nur Aqilah Pawancheek's interesting analysis of the difficulties surrounding the legal regime of Halal certification for the food and beverage industry in Malaysia, where problems abound regarding conflicts of jurisdiction between the Federal and State legislature under the Constitution, compounded by JAKIM's practices in the issuance of Halal certificates. Dr. Sharifah Suhanah Syed Alunad Executive Editor